Mobile Phone in Stomach—Is Endoscopic Trial Worthwhile?: A Case Report - Pawar, Ankush; Dalal, Ashok; Dahale, Amol; Sachdeva, Sanjeev; Puri, Amarender Singh (Journal of Digestive Endoscopy, 2020)
A 35-year-old male prisoner with a history of mobile phone ingestion was refereed to our center for management. Clinical examination was unremarkable. After confirmation on abdominal X-ray, we removed it endoscopically without any complication. To the best of our knowledge, this is only the second case report of successful endoscopic removal of mobile phone.
Keywords: endoscopy; foreign body ingestion; Gastric foreign body